Governments’ Measures to Govern the Coronavirus Crisis and the Lessons Learned - Sulaiman, Saqer (Public Governance, Administration and Finances Law Review, 2021)
Since its appearance in late 2019 in China, the Coronavirus pandemic has posed a real challenge to humanity and governments. No country was safe from the effects of the virus, whether from a medical, economic, or social point of view. In the absence of international coordination, countries began to rely on their own capabilities to curb the pandemic and mitigate its negative effects. To achieve these goals, different strategies and measures have been adopted. Despite the challenges governments faced, these measures definitely helped alleviate the severity of the epidemic and slowed its spread. These measures include, but are not limited to, lockdown, border restrictions, home quarantine, the imposition of wearing masks and social distancing. This crisis stresses the importance of a country’s financial, technical and human capabilities in governing crises. Moreover, it revealed that the absence of international cooperation in managing international crises has dire consequences for the international community.